Tiga Pilar Sukses: Perilaku Kewirausahaan, Etika Bisnis, dan Modal Sosial Untuk Meningkatkan Kinerja Bisnis - Didit Darmawan; Abdul Hafidz Rosydi Fuady; Rahayu Mardikaningsih; Eli Retnowati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Competition in the business world is increasingly fierce, making entrepreneurs look for the right strategy to market their products. This research aims to analyze factors that can improve business performance, namely entrepreneurial behavior, business ethics and social capital. The research method used was ex post facto with a questionnaire given to owners and managers of micro businesses in Waru District, Sidoarjo Regency. The collected data was analyzed using the regression method to test the influence of the independent variables, namely entrepreneurial behavior, business ethics and social capital, on the dependent variable, namely micro business performance. The results of the study show that entrepreneurial behavior has a significant positive effect on micro business performance. This shows that being proactive, innovative, and oriented to business opportunities can improve micro business performance. In addition, business ethics also have a significant positive influence on micro business performance, demonstrating the importance of operating with integrity and following ethical principles in running a business. Finally, social capital has also been shown to have a significant positive influence on micro business performance, indicating that social networks and relationships between micro business owners and related parties can increase access to resources and business opportunities